Phosphorescent [3 + 2 + 1] coordinated Ir(iii) cyano complexes for achieving efficient phosphors and their application in OLED devices. Issue 30 (7th July 2021) - Wu, Yuan; Yang, Chen; Liu, Jie; Zhang, Meng; Liu, Weiqiang; Li, Wansi; Wu, Chengcheng; Cheng, Gang; Yang, Qingdan; Wei, Guodan; Che, Chi-Ming
Abstract : Construction of [3 + 2 + 1] coordinated iridium(iii ) cyano complexes for achieving high-efficiency phosphors and their application in blue OLEDs with low efficiency roll-off. Abstract : A series of neutral [3 + 2 + 1] coordinated iridium complexes bearing tridentate bis-NHC carbene chelates (2, 6-bisimidazolylidene benzene), bidentate chelates (C^N ligands, e.g. derivatives of 2-phenylpridine), and monodentate ions (halides and pseudo-halides, such as Br, I, OCN and CN ions) have been systematically designed and synthesized. X-ray single crystal structure characterization revealed that the nitrogen atom in C^N ligands is located trans to the carbon atom in the benzene ring in tridentate chelates, while the coordinating carbon atom in C^N ligands is located trans to the monodentate ligands. Photophysical studies reveal that the C^N ligands play a vital role in tuning the UV absorption and emission properties, while the tridentate bis-NHC carbene chelates influence the lowest absorption band and emission energy when compared to heteroleptic Ir(ppy)2 (acac) [ i.e. molar absorptivities at ∼450 nm for ppy-OCN and Ir(ppy)2 (acac) are 350 M −1 cm −1 and 1520 M −1 cm −1 and emission maximum peaks are at 465 nm and 515 nm respectively]. Among monodentate ligands that the complexes bear, the group containing the cyanide ligand displays higher emission energy, higher photophysical quantum yields, longer triplet lifetimes and better electrochemical and thermal stabilities than those of cyanate and bromide. Particularly, a blue organic light-emitting diode (OLED) based on dfppy-CN exhibited a maximum external quantum efficiency of 22.94% with CIE coordinates of (0.14, 0.24). Furthermore, a small efficiency roll-off of 5.7% was observed for this device at 1000 cd m −2 .